Identification of an electrostatic ruler motif for sequence-specific binding of collagenase to collagen - Subramanian, Sundar Raman; Singam, Ettayapuram Ramaprasad Azhagiya; Berinski, Michael; Wade, Rebecca C. (The journal of physical chemistry. B, Biophysics, biomaterials, liquids, and soft matter, 2016)
Sequence-specific cleavage of collagen by mammalian collagenase plays a pivotal role in cell function. Collagenases are matrix metalloproteinases that cleave the peptide bond at a specific position on fibrillar collagen. The collagenase Hemopexin-like (HPX) domain has been proposed to be responsible for substrate recognition, but the mechanism by which collagenases identify the cleavage site on fibrillar collagen is not clearly understood. In this study, Brownian dynamics simulations coupled with atomic-detail and coarse-grained molecular dynamics simulations were performed to dock matrix metalloproteinase-1 (MMP-1) on a collagen IIIα1 triple helical peptide. We find that the HPX domain recognizes the collagen triple helix at a conserved R-X11-R motif C-terminal to the cleavage site to which the HPX domain of collagen is guided electrostatically. The binding of the HPX domain between the two arginine residues is energetically stabilized by hydrophobic contacts with collagen. From the simulations and analysis of the sequences and structural flexibility of collagen and collagenase, a mechanistic scheme by which MMP-1 can recognize and bind collagen for proteolysis is proposed.